Impact of Zakat Distribution Channels on Poverty Alleviation in Indonesia - Wasalmi, Wasalmi (Sinergi International Journal of Islamic Studies, 2024)
This study examines how different ways of distributing Zakat affect reducing poverty in Indonesia, with a focus on how effective Zakat groups are, the role of the government, public awareness, and the availability of Zakat monies. An investigation that involves 150 varied participants explores the connections between these parameters using Structural Equation Modeling with Partial Least Squares. The findings show important connections between effective Zakat groups, government assistance, public knowledge, availability of Zakat, and reducing poverty. The research offers important information for decision-makers, Zakat groups, and the general public to improve the impact of efforts to reduce poverty by making strategic changes in how organizations operate, government policies, social campaigns, and the availability of Zakat funds. Although this study offers useful information, there are several drawbacks, such as the possibility of bias in self-reported data and the ever-changing nature of socio-economic indicators. In the future, studies might look into the lasting effects of zakat distribution methods and examine how cultural and regional differences affect the success of poverty reduction efforts